Therapeutic vs. Suprapharmacological Metformin Concentrations: Different Effects on Energy Metabolism and Mitochondrial Function in Skeletal Muscle Cells in vitro - Pavlovic, Kasja; Krako Jakovljevic, Nina; Isakovic, Andjelka M.; Ivanovic, Tijana; Markovic, Ivanka; Lalic, Nebojsa M. (Frontiers in Pharmacology, 2022)
Metformin is an oral antidiabetic agent that has been widely used in clinical practice for over 60 years, and is currently the most prescribed antidiabetic drug worldwide. However, the molecular mechanisms of metformin action in different tissues are still not completely understood. Although metformin-induced inhibition of mitochondrial respiratory chain Complex I and activation of AMP-activated protein kinase have been observed in many studies, published data is inconsistent. Furthermore, metformin concentrations used for in vitro studies and their pharmacological relevance are a common point of debate. The aim of this study was to explore the effects of different metformin concentrations on energy metabolism and activity of relevant signaling pathways in C2C12 muscle cells in vitro. In order to determine if therapeutic metformin concentrations have an effect on skeletal muscle cells, we used micromolar metformin concentrations (50 µM ), and compared the effects with those of higher, millimolar concentrations (5 mM), that have already been established to affect mitochondrial function and AMPK activity. We conducted all experiments in conditions of high (25 mM) and low glucose (5.5 mM) concentration, in order to discern the role of glucose availability on metformin action. According to our results, micromolar metformin treatment did not cause Complex I inhibition nor AMPK activation. Also, cells cultured in low glucose medium were more sensitive to Complex I inhibition, mitochondrial membrane depolarization and AMPK activation by millimolar metformin, but cells cultured in high glucose medium were more prone to induction of ROS production. In conclusion, even though suprapharmacological metformin concentrations cause Complex I inhibition and AMPK activation in skeletal muscle cells in vitro, therapeutic concentrations cause no such effect. This raises the question if these mechanisms are relevant for therapeutic effects of metformin in skeletal muscle.